Pengaruh Tingkat Pengangguran Terhadap Tingkat Kemiskinan di Kabupaten Manggarai Barat - Hadim, Viktoria (Ekspektasi: Jurnal Pendidikan Ekonomi, 2024)
This research aims to determine the effect of the unemployment rate on the poverty rate in West Manggarai district. The data used in this research is secondary data from BPS in West Manggarai in 2016-2020. Data analysis using regression was then analyzed using SPSS 16.0., R=0.532, meaning that the independent variable unemployment rate was able to explain the value of the dependent variable by 5 3.2%, the remaining 46.8% was influenced by other factors. The R square value is 0.283 or 28.3 percent, while the remaining 71.7 percent is influenced by other variables. The research results show that the unemployment rate has no or no significant effect on the poverty level in West Manggarai district.